Design solutions for Lithuanian gravel road pavements - Čygas, Donatas; Žilionienė, Daiva (Journal of Civil Engineering and Management, 2002)
This article deals with the design problems of gravel road pavements. Mathematical models related to geological and hydrological conditions of a location, thickness of gravel pavement and characteristics of the gravel contained in this pavement are proposed to be used for pavements. For the selection of gravel pavements for reconstruction we recommend the models developed by the method of experimental planning to calculate the equivalent deformation modulus of the gravel pavements change depending on the deformation modulus of the subgrade, thickness of the gravel pavement and the materials used for its layers. Practical applications of these models will eliminate the mistakes that are still found in road pavement design.Frist Published Online: 30 Jul 2012